Automated software test control of speed-power capabilities - Корягин, В. М.; Блавт, О. З. (Physical Education Theory and Methodology, 2013)
An aim of work is development of electronic CAS of monitoring of speed-power possibilities engaging in a physical culture and sport. The questions test the level of speed-power capacity in the process of fitness. The technique of determining the level of speed-power capabilities using the touch electronic non-contact measurement. First demonstrated the feasibility and effectiveness of its use in sports and physical culture to enable rapid collection of reliable test data. In the presented work new approach is offered qualitatively to the problem of estimation of speed-power capabilities engaging in a physical culture and sport. Introduction and use of modern electronic technologies in a training process are powerful methodological basis for scientifically reasonable his purposeful continuous correction on the basis of the integral going near development of physical qualities, that allows to attain his quality improvement.